AquaNet - Disinfection byproduct parameters from Bolmen AquaNet platform - Bolmen Research Station (Sweden Water Research, 2024)
Data contains disinfection byproduct formation potentials analyzed from grab samples taken from the AquaNet mesocosms.
Bolmen Research Station (2024). AquaNet - Disinfection byproduct parameters from Bolmen AquaNet platform, 2022-07-07–2022-08-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Jh_1Jn64x-pPvaTWnROZDPVq
Keywords: SITES AquaNet; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap